2018
DOI: 10.1186/s12882-018-1025-z
|View full text |Cite
|
Sign up to set email alerts
|

A large, international study on post-transplant glomerular diseases: the TANGO project

Abstract: BackgroundLong-term outcomes in kidney transplantation (KT) have not significantly improved during the past twenty years. Despite being a leading cause of graft failure, glomerular disease (GD) recurrence remains poorly understood, due to heterogeneity in disease pathogenesis and clinical presentation, reliance on histopathology to confirm disease recurrence, and the low incidence of individual GD subtypes. Large, international cohorts of patients with GD are urgently needed to better understand the disease pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…From literature data, it has been hypothesized that the permeability factor may lead to the loss of nephrin and to the reduction of the expression of podocin [ 74 ]. Indeed, mutation of the gene NPHS2 which encodes for podocin, is associated with familiar and sporadic FSGS and the rate risk of recurrence in patients with this mutation is around 8%, contrary to the belief that familiar forms of FSGS do not recur [ 75 ]. In particular, suPAR seems to alter podocyte cytoskeleton and podocyte attachment with activation of beta 3-integrin and STAT1 in vascular smooth muscle cells through a PDGF receptor [ 76 ].…”
Section: Focal and Segmental Glomerulosclerosis (Fsgs)mentioning
confidence: 99%
See 1 more Smart Citation
“…From literature data, it has been hypothesized that the permeability factor may lead to the loss of nephrin and to the reduction of the expression of podocin [ 74 ]. Indeed, mutation of the gene NPHS2 which encodes for podocin, is associated with familiar and sporadic FSGS and the rate risk of recurrence in patients with this mutation is around 8%, contrary to the belief that familiar forms of FSGS do not recur [ 75 ]. In particular, suPAR seems to alter podocyte cytoskeleton and podocyte attachment with activation of beta 3-integrin and STAT1 in vascular smooth muscle cells through a PDGF receptor [ 76 ].…”
Section: Focal and Segmental Glomerulosclerosis (Fsgs)mentioning
confidence: 99%
“…Furthermore, the duration of dialysis and the type of post-transplant immunosuppression seem to be risk factors of recurrence [ 110 ]. A recent study by TANGO project group demonstrated that idiopathic FSGS recurs post-transplant in one third of cases and is associated with a five-fold higher risk of graft loss; moreover, the authors demonstrated that a response to treatment was associated with significantly better outcomes achieved in only half of the cases analyzed [ 75 ].…”
Section: Focal and Segmental Glomerulosclerosis (Fsgs)mentioning
confidence: 99%
“…Renal transplantation is a matter of concern in patients with FSGS as the general rate of recurrence is high (Uffing et al, 2018). Although three women of the 2nd generation were submitted to renal transplantation, none of them presented recurrent FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the heterogeneous treatment response suggests the opportunity to design a larger multicenter study in C3 GP patients after kidney transplantation. For this reason in 2017, a group of researchers across Europe and North and South America initiated the post-TrANsplant GlOmerular (TANGO) disease study, an observational multicenter cohort study with the aim to enroll patients who arrived to ESKD for different forms of glomerulonephritis, mainly C3 GP [64].…”
Section: Recurrence or De Novo C3 Gp After Kidney Transplatationmentioning
confidence: 99%